Modelling the factors of workplace spirituality in healthcare organization - Sankar, Hemanth; Suresh, M (International Journal of Engineering and Technology, 2018)
The term spirituality has got gravid and diverse meanings than we observe and most often it got confused with religion. Spirituality and religion are not identical and has different connotations. It is considered as an important entity in every organization as it can productively contribute in uplifting the work systems. The objective of this paper is to understand various spirituality factors influencing at work systems in hospitals. In order to study this, Interpretive Structural Modelling (ISM) approach is used to analyse the relationship among the factors of workplace spirituality. The paper projects forwards the most influential factors of workplace spirituality as pro-environmental behavior, job overload, and environmental passion which influence to its fullest in regulating the efficiency of the system, especially hospitals.Â Â